Traditional Phyto-remedies Used by the Midwives for the Treatment of Uterine Prolapse in Billawar and Basohli Tehsils of District Kathua, Union Territory of Jammu and Kashmir, India - Paul, Yash; Farooq, Bilques; Manhas, R. K. (Indian Forester, 2024)
When the uterus pushes into the vaginal canal as a result of the uterine ligament and fascial support tissue failing, this condition is known as uterine prolapse. It can be cured though traditional treatment in initial stages. The aim of this study was to document traditional methods used by the midwives to cure the prolapsed uterus in Billawar and Basohli tehsils of Kathua district, Union Territory of Jammu and Kashmir. Information was gathered from 25 traditional midwives (Dai), through semi-structured interviews. Uses of plants narrated by the informants were recorded as use-reports and further analysed for use-values. A total of seven plants from seven families, along with cinnabar (HgS) were used to cure a prolapsed uterus. Herbs and trees, with 42.9% contribution each, were the most commonly used life-forms, and seeds and leaves were the most preferred plant parts. The chief mode of medicine intake was the insertion of medicine into the uterus through vagina. Midwives suggested four treatments for uterine prolapse, primarily utilizing Quercus infectoria Oliver, Myristica fragrans Houtt., and Trigonella foenumgraecum L., along with massage and exercise. According to midwives, the time taken to recover varies with the age of the patient, her day-to-day activities, diet, and body setup. Use of Syzygium aromaticum (L.) Merr. & L.M. Perry, Papaver somniferum L., and Vitex negundo L., is new for the treatment of prolapsed uterus. Phytochemistry and pharmacological efficacy of these plants with respect to uterine prolapse, as well as the toxic effects of external use of cinnabar can be done in future.